Surface plasmon resonance biosensor for the detection of phenylethanolamine A in swine urine. Issue 10 (24th February 2021) - Fan, Sufang; Li, Chunsheng; Ma, Junmei; Meng, Zhijuan; Zhao, Limin; Zhang, Yan
Abstract : In this experiment, Au-NP sensor chip was prepared and used in the determination of phenylethanolamine A (PEA) in surface plasmon resonance (SPR). Abstract : In the present study, an antibody against phenylethanolamine A (PEA) was produced, confirmed, and used in a surface plasmon resonance (SPR)-based measurement. Bovine serum albumin (BSA)-conjugated PEA was linked to nano-gold particles bound to l -cysteine modified on the surface of a Au-NP sensor chip. The concentrations of antigen and antibody were optimized, and the designed biosensor chip was investigated to examine the stability and accuracy of the proposed method. The recovery of PEA ranged from 80.4–93.4% in swine urine samples with spike levels of 5, 10 and 20 ng mL −1, and the relative standard deviations of PEA were less than 2%. PEA analogues, such as clenbuterol, ractopamine, and salbutamol, did not influence the PEA measurement. The developed method could be used to measure PEA in swine urine samples.